Self-employment, wage employment and informality in a developing economy - John Bennett; Matthew D. Rablen (Institute for the Study of Labor (IZA), 2012)
We construct a simple model incorporating various urban labour market phenomena obtaining in developing economies. Our initial formulation assumes an integrated labour market and allows for entrepreneurship, self-employment and wage employment. We then introduce labour market segmentation. In equilibrium voluntary and involuntary self-employment, formal and informal wage employment, and formal and informal entrepreneurship may all coexist. We illustrate the model by an example calibrated on Latin American data, examining individual labour market transitions and implications of education/training and labour market policies. To diminish informality, cutting the costs of formality is more effective than raising those of informality.
urn:nbn:de:101:1-201206146915
Keywords: O17; J23; 330; self-employment; wage employment; informality; Städtischer Arbeitsmarkt; Selbstständige; Arbeitskräfte; Schwarzarbeit; Unternehmer; Informeller Sektor; Arbeitsmarktsegmentierung; Theorie; Lateinamerika